Comparative study of micro topography on laser ablated C/SiC surfaces with typical uni-directional fibre ending orientations. Issue 7 (15th May 2016) - Wu, M.L.; Ren, C.Z.; Xu, H.Z.
Abstract: Functional micro-structures on laser-ablated carbon fibre reinforced composites surfaces exhibit distinct advantages. A variety of fibre endings with different orientations may coexist on the C/SiC sectional plane, the anisotropic nature of C/SiC (carbon fibre reinforced silicon carbide) composites present a new challenge to the laser ablation process. However, few reports describing the influence of the fibre ending orientations on the laser-ablated C/SiC surface topography could be found. In this investigation, micro-ridges were established on three typical C/SiC surfaces by laser ablation, and a comparative study was performed to identify the topography variations on these laser-ablated C/SiC surfaces. The results showed that C/SiC surfaces with different fibre ending orientations present distinct surface characters ( Sz, Sq ) after laser ablation. Although all of the laser ablation processes are similar in nature, the fibre ending variation made the laser and material interaction different greatly. Attention should be devoted to the influence of the fibre ending orientation on surface topography formation before performing the laser ablation of carbon fibre reinforced composite materials. Finally, some typical surface defects on these laser-ablated surfaces were also discussed.